A PRODUÇÃO DA ESCALA METROPOLITANA E DO SEU PESQUISADOR: ELEMENTOS DE RITMANÁLISE - Martins, Flávia Elaine da Silva (GEOUSP Espaço e Tempo (Online), 2009)
This article seeks to understand the production of the metropolitan area from the extension of credit agreements and debt in the composition of urban real estate. Are approaches in this context the opening of capital in real estate development and the presence of auction properties and real estate agents. The production scale of the property being marketed by developers and scope of the metropolitan scale and location of these launches put the social production of urban scale as feature to search for in geography from the researcher that includes your daily source of research.